Hot Spots of Commercial Sex Activities in New York City Neighborhoods: Lessons Learned - Suh, Brittany (Crime & delinquency, 2024)
Understanding the spatial distribution of commercial sex activities (CSA) in urban environments is important in addressing the harms against sex workers and identifying sex trafficking operations. Guided by crime pattern theory, using Census data and New York Police Department (NYPD) prostitution-related arrests data (N = 29,075) from 2010 to 2019, this study examines the “hot spots” of CSA in New York City. Local Spatial Autocorrelation Analysis (LISA) identified distinctive spatial clusters of CSA, whereas logistic regression explained their significant congregation in immigrant and racial-ethnic enclaves. The heterogeneity of clusters by boroughs portrays the convergence of activity space of sex workers, patrons, and sex business opportunities reflecting the high-demand locations of CSA and human trafficking in NYC.